Agricultural Marketing in Rural Areas of Dakshina Kannada District-problems and Policy Measures - Raghurama, A. (Indian Journal of Marketing, 2005)
Dakshina Kannada District is located in the Western coast of Karnataka, almost half way between Bombay and Cape Comorin. It is a narrow strip of land stretching 60 kilometres from North to South and spreads 70 kilometres from East to West in the form of a low lying, broken plateau from the Western Ghats to the Arabian sea. The district has been divided into two geographical regions viz. The Coastal region consisting of Mangalore Taluk with a coastal line of 60 kilometers and the Malnad region comprising of Belthangady, Puttur, Sullia and Bantwal taluks.The total area of coverage of the district is 4,866 sq. kilometers.